Patient injuries from tonsil and adenoid surgery in Finland - Sjöblom Henrik M.; Timgren Jaakko M.; Piitulainen Jaakko M.; Jero Jussi (WILEY, 2022)
Objectives: The aims of this national register-based study were to examine patient injury claims related to tonsil and adenoid surgery injuries and to compare the frequency of claims between tonsillectomies and tonsillotomies in Finland.
Methods: We analyzed the complaints related to tonsil and adenoid surgery received by the Finnish Patient Insurance Center (PIC) between the years 2000 and 2019. One hundred seventy-two cases were included in the analysis. The annual surgery rates between the years 2000 and 2018 were acquired from the Finnish Institute for Health and Welfare.
Results: During the years 2000 to 2018, a total of 292,679 patients had tonsil and/or adenoid surgery nationwide. For tonsil or adenoid surgeries, the national average was 5.3 cases and 1.8 cases per 10,000, respectively, resulting in patient injury claims and compensations. A total of 33.1% of the claims regarding tonsil or adenoid surgery processed by the PIC were compensated. Most of the claims were made after a tonsillectomy (87.8%), and few were made after a tonsillotomy (1.7%). Seven deaths were recorded.
Conclusion: Patient injuries from tonsil and adenoid surgeries were mostly related to traditional extracapsular tonsillectomies. Most surgeries, along with most complications, involved specialists, who performed routine operations in high-volume centers. Surgeries for acute or recurrent infections resulted in more claims. Severe complications arising from tonsil and adenoid surgeries were rare.
Level of Evidence: 4.